A study of the salary standardization laws with emphasis on position classification system - Lalisan, Danibell G. (2003)
Pay determination is a difficult task. This is because pay has a monetary value which is important to employees because pay check is often the sole means of economic survival. It is also one of the most influential factors in determining status in society. On the part of the organization (government), a good compensation program is necessary in order to attract capable employees to the organization, to motivate them toward superior performance, and to retain their services over an extended period time. A properly designed compensation program therefore is recommended in order to achieve desirable outcomes for the best interest of both employees and the organization. Towards this end, compensation must be fair and equitable coupled with fair procedures in administering the pay plan. The focus of this study is the Position and Classification System or the Pre-Determined Grade System applied by the government in structuring the classification and compensation plan as provided for in the two standardization laws enacted by the Philippine Congress. These two laws are the Compensation and Position Classification Act of 1989 (RA 6758) and the Joint Resolution urging the President of the Philippines to revise the existing compensation and classification system in the government and to implement the same initially effective January 1994 (Resolution no.01,s.1994). How the government arrived to the enactment of the standardization laws can be attributed to the disparities in the salary of the civil servants in the country which brought about dissatisfaction in the government's pay policy. This situation paved the way for the inclusion in the provisions of the 1973 Constitution for the standardization of the compensation of government officials and employees including those in government-owned or controlled corporations. Thus, RA 6758 and Joint Resolution no.01, were enacted and compensation plan was designed to achieve the policy of the State "to provide equal pay for substantially equal work and to base differences in pay upon substantive difference in duties and responsibilities, and qualification requirements of the position.Whether the aforecited objectives are attained is the focus of this study. Using the positions of Court Legal Researchers II of the Regional Trial Courts and Public School Teachers as the subjects of study, the problems in the administration and implementation of the Position Classification System which is the job evaluation method employed by the government in designing the pay plan, are unveiled. The issues and problems concern the process or procedure in determination of salary grades, the limited listings of comparable positions in the Benchmark Position Schedule as provided for under RA 6758 and joint resolution no.01,s. 1994 (the law revising RA 6758), the lack of participation of the incumbents in designing the pay plan,the determination of qualification standards of the positions without unified actions of the Civil Service Commission, DBM and the agency and lack of information of the incumbents in the nature or features of the Position Classification and Compensation Plan are among the problems culled from the case studies, In order to remedy the aforestated problems, this study has come up with several recommendations to wit:...
A paper submitted in partial fulfillment of the course requirements of P.A. 247 (Policy paper)
"October 2003."
Keywords: Wages -- Law and legislation -- Philippines; Job evaluation -- Philippines; Civil service positions -- Philippines -- Classification